The vascularity of internal fistulae in Crohn's disease: an in vivo power Doppler ultrasonography assessment. Issue 4 (1st April 2002) - Maconi, G; Sampietro, G M; Russo, A; Bollani, S; Cristaldi, M; Parente, F; Dottorini, F; Bianchi Porro, G
Abstract : Aim: To evaluate the efficacy of power Doppler sonography (US) in depicting internal fistulae and their vascularity, and to study the characteristics of blood flow within the fistula wall. Patients and methods: The study involved 45 consecutive patients with Crohn's disease and suspected internal fistulae detected by grey scale US. The fistulae were subsequently evaluated using power Doppler US to reveal any areas of increased vascularity, and the results were compared with radiographic, endoscopic, or intraoperative findings. Whenever feasible, we also performed spectral analysis of blood flow revealed by power Doppler US, calculated its resistance index (RI), and analysed its characteristics, reproducibility, and relationship with biochemical and clinical variables (Crohn's disease activity index, disease duration, location, and abdominal complications). Results: Power Doppler US revealed vascularity in all of the internal fistulae that where subsequently confirmed by diagnostic procedures. In the case of intra-abdominal abscesses in the vicinity of the fistula, vascular signals were detected mostly around and not within the lesions. The intensity and distribution of the signals differed within the fistulae tracks and had only slight day to day reproducibility; furthermore, there was no significant correlation with clinical or biochemical variables. Spectral analyses of blood flow within the fistulae revealed arterial flow in 96.7% of patients (median RI 0.715). RI was a more reproducible parameter and significantly correlated with clinical ( r = 0.54) and biochemical activity ( r = 0.56) of CD. It was also higher in fistulae complicated by abscesses. Conclusion: Power Doppler US can reveal the presence of vasculature within the wall of internal fistulae and therefore enhance grey scale US performance. The RI characteristics of blood flow within the fistulae are reproducible and correlate with biochemical and clinical disease activity.